Interleukin-6 and Tumour Necrosis Factor-α differentially regulate lincRNA transcripts in cells of the innate immune system in vivo in human subjects with rheumatoid arthritis - Müller, Nike; Döring, Frank; Klapper, Maja; Neumann, Katrin; Schulte, Dominik M.; Türk, Kathrin; Schröder, Johann O.; Zeuner, Rainald A.; Freitag-Wolf, Sandra; Schreiber, Stefan; Laudes, Matthias (Cytokine (Philadelphia, Pa.), 2014)
•lincRNAs are transcripts from non-coding DNA.•We found that IL-6 and TNF-α regulate different types of lincRNAs in vivo.•Our data suggest a role for lincRNA in the pathophysiology of RA.•Our data indicate lincRNAs to be specifically regulated by pharmaceutical agents. lincRNAs recently have been discovered as evolutionary conserved transcripts of non-coding DNA sequences and have been implicated in the regulation of cellular differentiation. In humans, molecular studies have suggested a functional role for lincRNAs in cancer development. The aim of the present study was to examine whether these novel molecules are specifically regulated by different cytokines in cells of the innate immune system in humans in vivo and whether lincRNAs thereby might be involved in the pathophysiology of rheumatoid arthritis (RA). Therefore, CD14+ monocytes were isolated from RA patients before and after anti-IL-6R (tocilizumab) or anti-TNF-α (adalimumab) therapy and lincRNA transcription was analysed by a microarray based experiment. As expected, we found lincRNAs to be present in CD14+ monocytes of RA patients. However, of the total number of 7.419 lincRNAs examined in this study only a very small number was significantly regulated by either IL-6 or TNF-α (85 lincRNAs, corresponding to 1.1%). The numbers of lincRNAs regulated was higher due to TNF-α compared to IL-6. Interestingly, none of the identified lincRNAs was influenced by both, IL-6 and TNF-α, suggesting the regulation of lincRNA transcription to be highly specific for distinct cytokines. Taken together, our results suggest (1) that lincRNAs are novel intracellular molecular effectors of specific cytokines in cells of the innate immune system in humans in vivo and (2) that lincRNAs might be involved in the molecular pathophysiology of RA.